Students' Attitudes Towards Learning Mathematics: "Too Soft Attitudes-Very Difficult-Boring-In A Good Way" - Darmayanti, Rani; Laila, Alfi Rachma Nisfi; Khan, Shahid; Fitriyah, Imamah Dien; Bausir, Umar; Setio, Agus; Usmiyatun, Usmiyatun (Indonesian Journal of Learning and Educational Studies, 2023)
Students' attitudes towards learning mathematics: "too soft attitudes-very difficult-bored-in a good way" is an expression that is described because of a problem. Difficulties in understanding mathematical concepts have an impact on poor problem-solving abilities, so it is important to know what causes students to make mistakes and difficulties in learning mathematics. The goal to be achieved through this research is to find learning problems, their causes, and how to overcome them in learning mathematics. The research method of this research is a qualitative research based on a phenomenological approach. This study was conducted at his MTs Darul Hikmah Kedungwaru in Tulungagung. The main data sources are students and teachers of mathematics. Sources of supporting data are the Head of MTs Darul Hikmah Kedungwaru and class teachers. Data collection techniques through observation and interviews. Data analysis techniques are data reduction, data presentation, and conclusion/validation. The results are as follows. (a) student problems: Lack of understanding of the material provided by the teacher, low student motivation to study, lazy to do homework regularly. (b) Educator's Problems: The teacher's inability to master the class, the teacher's inability to master the learning material. Efforts to overcome problems learning mathematics: (a) Efforts to Solve Student Problems: Strive to improve the learning environment Attempt to motivate students by providing suggestions to help them learn more actively Reward students with grades and praise for their learning Remind them to complete their homework (b) Efforts to solve educator problems, namely: Schools conduct assessments, summon teachers who are unable to attend class, and conduct teacher coaching and training, especially math teachers